2004
DOI: 10.1111/j.1523-1755.2004.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Static intra-access pressure ratio does not correlate with access blood flow

Abstract: SIAPR does not correlate with Qa or discriminate between high and low Qa. Therefore, because the utility of SIAPR surveillance for detection of clinically significant stenosis depends on a correlation with Qa, the current use of absolute K/DOQI SIAPR thresholds for intervention based on the presumption that such thresholds are indicative of low Qa is not justified, and should be discontinued. Studies need to be done to examine the utility of SIAPR for trend analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…As further confirmation, we can compare the model with clinical data on the relation between VP/MAP and Q ( Figure 9) (22). The scatter in Figure 9 is wider than that in Figure 8, but this difference is easily explained.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…As further confirmation, we can compare the model with clinical data on the relation between VP/MAP and Q ( Figure 9) (22). The scatter in Figure 9 is wider than that in Figure 8, but this difference is easily explained.…”
Section: Discussionmentioning
confidence: 71%
“…Besarab et al (20,33) found that a high VP/MAP is associated with low Q, whereas Spergel et al (22) found no correlation between VP/MAP and Q (Figure 9). Thus, we used the model to examine the relation between these variables.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations